Heterolytic cleavage of the B–H bond in H3B·L (L = THF, NMe2H) by an electrophilic Ir(iii) pincer complex [Ir(H)(PMe3)(tBu4POCOP)][BAr F4] - Pradhan, Mitarani; Surati, Zeel Y.; Pal, Apurba Kumar; Vanka, Kumar; Jagirdar, Balaji R. (2025)
<div class="abstract author" id="aep-abstract-id6" style="box-sizing: border-box; margin: 0px 0px 8px; padding: 0px; color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;"> Six- and five-coordinate iridium complexes, [Ir(H)Cl(PMe3)(tBu4POCOP)] (2) (tBu4POCOP = κ3-C6H3-2,6-(OPtBu2)2) and [Ir(H)(PMe3)(tBu4POCOP)][BArF4] (3), respectively, have been synthesized and characterized. The reactivity of the electrophilic 16-electron iridium(III) complex 3 with H2, H3B·THF, H3B·NMe2H, and H3B·NMe3 was investigated. The reaction of complex 3 with H2 resulted in the formation of trans-[Ir(H)(η2-H2)(PMe3)(tBu4POCOP)][BArF4] complex 5. Complex 3 was found to activate the B–H bonds in H3B·THF and H3B·NMe2H (DMAB) in a heterolytic fashion. The reaction of complex 3 with H3B·THF at 298 K afforded trans-[Ir(H)2PMe3(tBu4POCOP)] complex 6 and a boronium compound, [H2B(THF)2][BArF4]. Monitoring the reaction from 179 to 298 K by NMR spectroscopy revealed the formation of a σ-borane intermediate, trans-[Ir(H)(η1-HBH2·THF)PMe3(tBu4POCOP)][BArF4] (3a-Int), en route to the final products observed at 298 K. The formation of this intermediate species was also investigated by density functional theory (DFT) calculations. The reaction of complex 3 with H3B·NMe2H at 298 K yielded a mixture of complexes 3 and 5 and a cyclic diborazane [H2BNMe2]2. The reaction was found to proceed via intermediates, a σ-borane complex, trans-[Ir(H)(η1-HBH2·NMe2H)PMe3(tBu4POCOP)][BArF4] (3b), complex 6, [(NHMe2)2BH2][BArF4], and H2B<img alt="[double bond, length as m-dash]" border="0" src="https://www.rsc.org/images/entities/char_e001.gif" style="border: none; color: rgba(0, 0, 0, 0.79); font-family: "Source Sans Pro", source-sans-pro, museo_sans300, museo-sans, Arial, sans-serif;" />NMe2. Complex 3 exhibited no reactivity with H3B·NMe3.